Jack and the beanstalk - Nesbit, E. (Edith), 1858-1924.; Tavares, Matt (Cambridge, MA : Candlewick Press, 2006)
A boy climbs to the top of a giant beanstalk, where he uses his quick wits to outsmart a giant and make his and his mother's fortune.
2.4
K-3
Keywords: Fairy tales; Giants -- Folklore; Folklore -- England; Fairy tales; Giants -- Folklore; Folklore -- England